2020
DOI: 10.1016/j.fuel.2019.116241
|View full text |Cite
|
Sign up to set email alerts
|

Dispersed phase structure and micro-explosion behavior under different schemes of water-fuel droplets heating

Abstract: One of the known and still unsolved problems of internal combustion engines and liquid fuel power plants is the complexity of efficient (i.e. with minimal cost of basic resources: time, energy and raw materials) ignition of fuels issued from valorization of waste. A promising way to improve the efficiency of ignition of liquid fuels is a secondary atomization using the micro-explosion of water-fuel droplets.This phenomenon is called micro-explosion when concerning an individual water-in-oil emulsion drop among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…The analysis of the phase separation process and the formation of a composite state of water in fuel is beyond the scope of the paper. These processes are discussed in many papers, including [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of the phase separation process and the formation of a composite state of water in fuel is beyond the scope of the paper. These processes are discussed in many papers, including [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the temperature within a droplet may be highly dependent on the heating scheme [32][33][34][35][36][37][38][39][40][41]. That is why all studies of such kind require specialized equipment and data processing algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…It is also important to select the optimal droplet heating scheme for these conditions. The analysis of various heating schemes [39,40] indicates that conductive heating (using a heated surface) is the optimal scheme for 2-Color LIF as compared to other heat exchange schemes. Radiative heating complicates the optical access to a droplet.…”
Section: Introductionmentioning
confidence: 99%
“…Good atomization effect plays an important role in flame spray pyrolysis (FSP), fluid catalytic cracking (FCC) and fuel combustion [1][2][3][4][5] . So, emulsified feedstock technique, which replaces the feedstock with water-in-oil (W/O) emulsions, is developed to try to use explosive boiling of lighter components (water) making the micro-explosion more intense 2,6,7 . Several studies have shown the potential of this emulsified feedstock technique in chemical production.…”
Section: Introductionmentioning
confidence: 99%